(untitled) (Archive of Conferences, 2021)
The North American exposition of plants of the North American dendroflora, which is of great interest to visitors of the Tashkent Botanical Garden, was organized in the autumn of 1950 and covers an area of 9 hectares. This dendroflora is located in the north-eastern part of the Botanical Garden. The organizer of the plant garden is academician F.N. It was propagated by Rusanov by importing seeds and vegetative parts of plants from the northern regions of America. The dendroflora includes species of trees and shrubs from North America, Canada and partly Mexico